Existências relâmpagos : medicalização em tempo integral - Abreu, Lorena Dias de (2016)
The main objective of this study was to discuss child medicalization practices in scholar environment. It was applied a research method based on field notes and narrative assemblage with boys and girls of school age. The aim was to highlight field experiences that represent thematic events of medicalization and pathologization of child behaviors. It was highlighted practices at the school environment, specifically at the full-time education, their nuances and its associations with children normalization intentions. It is discussed the historical constitution of the medical knowledge-power expansion and the consequent childhood capture. By the stories lived, the researchers identified the medicalization process as a way of appeasement of differences. Along with consume culture and its new technologies, the medicine consume became ordinary and popular, supported by the expansion of the pharmaceutical industry, one of the most rentable and promising business fields in actuality. Considering the education area, it would be impossible to not consider the Attention Deficit Hyperactivity Disorder (ADHD) and its respective medicine, Ritalin. This combination requires the discussion of a disease construction and the promulgation of a specific diagnostic with the intention of drug media propagation.